Relationship between the Chinese visceral adiposity index and gout in individuals with type 2 diabetes mellitus: a cross-sectional population-based study - Cai, Ningyu; Chen, Mengdie; Feng, Ping; Wang, Yiyun; Zhu, Xianping; Zheng, Qidong (Frontiers in Nutrition, 2025)
BackgroundVisceral adiposity indices have recently attracted considerable attention in metabolic and cardiovascular research. Here, the link between the Chinese Visceral Adiposity Index (CVAI) and gout in individuals with type 2 diabetes mellitus (T2DM) was investigated.MethodsThis cross-sectional analysis evaluated 14,099 adults with T2DM. The CVAI-gout relationship was investigated using restricted cubic spline (RCS) modeling to assess dose-responsiveness. Multivariable logistic regression was applied, with adjustments for demographic and metabolic covariates. Subgroup analyses and interaction tests were performed across clinically relevant strata, and ROC curves were applied to assess the utility of the CVAI in discriminate patients with gout.ResultsAmong all participants, 5.7% were diagnosed with gout. Higher CVAI values were linked with raised gout incidence (adjusted OR 1.07, 95% CI 1.05–1.09), with RCS models revealing a steadily increasing, positive association between between the CVAI and gout prevalence. After full adjustment, the top CVAI quartile showed a 2.44-fold greater prevalence of gout (95% CI 1.85–3.22) relative to the lowest quartile. Subgroup analyses confirmed consistent associations across various categories. ROC analysis further demonstrated that CVAI had superior discriminative ability for gout compared with traditional obesity indices.ConclusionThis large-sample investigation of Chinese patients with T2DM indicated a strong positive link between the CVAI and gout, suggesting the potential of the CVAI for stratifying metabolic risk in this population.